Visual Impairments Are Associated With Retinal Microvascular Density in Patients With Parkinson’s Disease - Zhou, Min; Wu, Lei; Hu, Qinyuan; Wang, Congyao; Ye, Jiacheng; Chen, Tingting; Wan, Pengxia (Frontiers in Neuroscience, 2021)
Objective: To evaluate retinal microvascular density in patients with Parkinson’s disease (PD) and its correlation with visual impairment. Methods: This cross-sectional study included 24 eyes of 24 patients with PD and 23 eyes of 23 healthy controls. All participants underwent ophthalmic examination, visual evoked potentials (VEP), 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25), and optical coherence tomography angiography (OCTA) examination. The correlation between retinal microvascular density and visual parameter was evaluated using Spearman correlation analysis and the area under receiver operating characteristic curve (AUROC) was calculated. Results: PD patients had prolonged P100 latency (P=0.041), worse vision-related quality of life (composite score and 3 of 12 subscales in NEI VFQ-25), and decreased vessel density (VD) in all sectors of 3 mm diameter region (all P<0.05) compared with healthy controls. There were no statistical differences in the ganglion cell-inner plexiform layer (GCIPL) thickness and retinal nerve fiber layer (RNFL) thickness between the two groups. A negative correlation was found between P100 latency and nasal and superior sectors of macular VD in 3 mm diameter region (r=-0.328, P=0.030; r=-0.302, P=0.047; respectively). Macular VD in 3 mm diameter region showed diagnostic capacities to distinguish PD patients from healthy controls (AUROCs, ranged from 0.655-0.723). Conclusion: This study demonstrated that decreased retinal microvascular density was correlated with visual impairment in PD patients. Retinal microvasculature change may occur earlier than visual decline and retinal structure change, and has the potential to be a promising diagnostic marker for early PD.